Pharmacist‐Led Intervention on the Inappropriate Use of Stress Ulcer Prophylaxis Pharmacotherapy in Intensive Care Units: A Systematic review - Xu, Peipei; Yi, Qiusha; Wang, Cuitong; Zeng, Linan; Olsen, Keith M.; Zhao, Rongsheng; Jiang, Mingyan; Xu, Ting; Zhang, Lingli (Frontiers in Pharmacology, 2021)
Background Pharmacists’ direct intervention or participation in multidisciplinary management teams can improve the clinical outcome and quality of life of patients. We aimed to determine the effectiveness of pharmacist-led interventions on the inappropriate use of stress ulcer prophylaxis (SUP) pharmacotherapy in intensive care units (ICUs). Methods A systematic review was performed for relevant studies using searched PubMed, EMBASE (Ovid), the Cochrane Library, Cochrane Central Register of Controlled Trials (CENTRAL), and four Chinese databases from the establishment of databases to 12 March 2020. We conducted a descriptive analysis of participants, the intervention content and delivery, and the effects on inappropriate medication rates. Results From 529 records, 8 studies from 9 articles were included in the narrative synthesis. The time of appropriateness judgment and the criteria of ‘appropriate’ varied from included studies. Pharmacist interventions mainly included clarifying indications for SUP pharmacotherapy, education and awareness campaign, reviewed patients on SUP pharmacotherapy during rounds, and adjustments of drug use. Five (62.5%) studies found a significant intervention effect during hospitalization, while 2 (25%) studies at ICU transfer and 2 (25%) studies at hospital discharge. Four (50%) studies identified the complications related to SUP pharmacotherapy and found no significant difference. Four (50%) studies declared the pharmacist-led interventions were associated with cost savings. Conclusion Pharmacist-led interventions may be associated with a decrease in inappropriate SUP pharmacotherapy rates during hospitalization, at ICU transfer and hospital discharged. Further research is needed to determine whether the latest guidelines are more suitable for the management of SUP pharmacotherapy and whether pharmacist-led intervention is cost-effective.